Functional limitation and happiness among older adults: the multiple mediating role of intergenerational support and intergenerational relationship - Zhou, Angdi; Song, Yiwen; Li, Xinru; Hu, Bingqin; Chen, Yitong; Cui, Peiyao; Li, Jinghua (Frontiers in Public Health, 2023)
Objectives This study aimed to investigate the relationship between the functional limitation and happiness among Chinese older people and examined the multiple mediating effects of intergenerational support (instrumental support and financial support) and intergenerational relationship. Method Data was drawn from the Chinese Family Panel Survey (CFPS) 2018 and 2020. Structural equation modeling was adopted to analyze the association among functional limitations, intergenerational support, intergenerational relationship, and the older adults happiness. Results There was a significant association between the functional limitations and the lower happiness levels among the older adults. The instrumental support from adult children positively mediated the relationship between the functional limitation and the happiness. However, intergenerational relationships were reduced due to the dysfunction of the older adults, and played a negatively mediated role between the functional limitation and the happiness. In addition, instrumental and financial support play chain-mediating roles between functional limitation and happiness in older adults through intergenerational relationships. Conclusion Intergenerational relationships and instrumental support enhance the happiness of older adults with functional impairments, but their role is limited by the changing structure of modern families. Long-term care programs combined with the intergenerational support from families for people with functional impairments in old age would be more effective to reduce the burden on adult children and maintain the quality of life of the older adults.